GeoConnect: An Immersive VR Game for Learning Brazilian Geography - Oliveira, Leticia Z. de; Domingues, Gustavo C.; Macedo, Jose Lucas H.; Peres, Fabiana F. F.; Mauricio, Claudio R. M.; Hayama, Ericson H. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15765, 2025)
GeoConnect is an educational VR game designed to support the development of cartographic skills through an immersive and interactive experience. Aligned with the competencies outlined in the BNCC, the game introduces progressively challenging puzzle stages focused on assembling the Brazilian map. Players interact with floating pieces using snapping mechanics, with multimodal feedback (visual, auditory, and haptic) reinforcing spatial learning. The objective of this work is to present the first version of GeoConnect and to evaluate its usability through a simplified structure that includes a 360° exploration mode for each completed region. The results indicate that the system successfully met its objective, delivering a functional prototype capable of supporting cartographic learning in an engaging way.